Monitoring the Performance of the Palestinian Security Apparatuses and its Role in Strengthen Freedom and Achieving Civil Peace - Marshoud, Basem Salem (Journal of Economic, Administrative and Legal Sciences, 2023)
The research aims to recognize the impact of monitoring on the Palestinian security services, to present an objective assessment of the performance of the Palestinian security services within various obstcales, and to offer a security vision and understanding that correspond with the concepts of political modernity The research problem focuses on the challenge of conducting the monitoring process under occupation. Moreover, it focuses on the impact of the monitoring process on the security services under the occupation. The researcher assumes that applying monitoring over the performance of the security forces is necessary in spite of the existence of obstacles imposed by the occupation. Thus, it contributes to the institutional construction and supports liberties and civil peace. The research adopts the analytical descriptive approach. The study is divided into an introduction, four chapters and a conclusion. One of the most important results of the research is that monitoring enhances national loyalty within the frame of partnership and cooperation between the citizens and the authorities. Monitoring imposes the principle of sovereignty of law. In addition, it deepens transparency and the principles of rational governance. It also introduces the concept of security which guarantees safety and welfare for the citizens. Moreover, monitoring the security bodies contributes to spreading freedom and achieving civil peace. Consequently, this would guarantee development and push it steps forward. The research presents several recommendations. Such includes issuing a presidential decree to assign an Inspector General over the security services with expanded supervisory powers, establishing a civil agency that supervises and monitors the army, security and military units. It also includes activation of internal and external monitoring with wide authorities and power, and putting into practice ending impunity of state officials، and emphasising the principle of responsibility and accountability. Moreover, recommendations include establishing an integral monitoring system with civil society.